Удосконалення конструкції біогазової установки з рекуперацією теплоти збродженої біомаси - Скляр, Олександр Григорович; Скляр, Радміла Вікторівна; Комар, Артем Станиславович; Sklіar, Oleksandr; Skliar, Radmila; Komar, Artem (Запоріжжя : ТДАТУ, 2024)
UA: В статті запропоновано установку та технологію для рекуперації теплоти збродженої біомаси, намічено основні вимоги до процесу тепловідбору та шляхи його інтенсифікації. Проведений аналіз витрат енергії на системи забезпечення процесу метаногенезу дозволив зробити висновок про те, що головну увагу при пошуку шляхів зниження енергоємності метанового зброджування слід приділяти системам рекуперації теплоти збродженого гною і перемішування біомаси в біореакторах. При цьому з огляду на інтенсивний спосіб обробки біомаси в термофільному режимі обрано рекуператор інтенсивної дії. Крім того, апарати, що вибираються, повинні задовольняти вимогам, які ставляться до установок, працюючих з неньютонівським характером рідини, до яких відноситься біомаса. Також наведено схему рекуператора, що працює в режимі зворотно-поступального руху фаз з пульсуючим завантаженням та вивантаженням біомаси. EN: The use of typical heat exchangers for heat utilization of manure, which is processed in a biogas plant, has the following difficulties: difficult operation due to the non-Newtonian nature of liquids; autonomous pumping equipment is required; the technologically limited loading time of the methane tank determines large volumes of heat exchangers. The structure of manure and the taxonomic dependence between different types of microorganisms limit the use of different types of recuperators and bioreactor designs, as well as mixing methods and increased manure movement speeds during anaerobic fermentation. mechanical mixing of the fermenting biomass negatively affects the normal cultivation of methane bacteria. The presence of oxygen in the original biomass, which mixes with the fermented biomass throughout the entire volume of the reactor, has a similar effect, as its inhibitory effect begins to manifest in this case. The article proposes an installation and technology for heat recovery of fermented biomass, outlines the main requirements for the heat extraction process and ways of its intensification. The conducted analysis of energy costs for systems supporting the methanogenesis process made it possible to conclude that the main attention when searching for ways to reduce the energy intensity of methane fermentation should be given to systems for recovering the heat of fermented manure and mixing biomass in bioreactors. At the same time, taking into account the intensive method of processing biomass in thermophilic mode, an intensive recuperator was chosen. In addition, the devices selected must meet the requirements for installations working with non-Newtonian fluids, which include biomass. Also given is the scheme of the recuperator operating in the mode of reciprocating phase movement with pulsating loading and unloading of biomass.
Improving the design of a biogas plant with heat recovery of fermented biomass
Keywords: рекуператор; теплообмін; гній; метанове зброджування; біомаса; інтенсифікація; recuperator; heat exchange; manure; methane fermentation; biomass; intensification